SYNTHESIS OF COMPLEX COMPOUNDS OF SOME 3D METALS WITH 6-AMINOPYRIDINE-2-CARBOXYLIC ACID AND THEIR APPLICATIONS. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Coordination chemistry is one of the most rapidly developing fields of modern inorganic chemistry. In particular, metal complexes formed on the basis of heterocyclic organic ligands containing nitrogen and oxygen atoms are widely used in various fields. This article analyzes the synthesis of complex compounds formed by 3d transition metals – copper (Cu), zinc (Zn), cobalt (Co), nickel (Ni) and iron (Fe) ions with 6-aminopyridine-2-carboxylic acid, their physicochemical properties, and potential practical applications.